2001
DOI: 10.2116/analsci.17.1425
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hydrogen Peroxide by Iron(III) Complex of Thiacalix[4]arenetetrasulfonate on a Modified Ion-Exchanger with Peroxidase-like Catalytic Activity1

Abstract: Calix [n]arenes are of much interest because of their high selectivity and specificity for forming host-guest complexes. 2,3 In analytical chemistry, various calix[n]arene derivatives have been developed by modifying either the upper or lower rim in order to apply them as analytical reagents for separations 4-7 and sensors 8-12 of various ions, molecules, and so on. It has been shown that recently developed thiacalix[n]arenes have a very interesting characteristic: an ability to form very stable metal complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…As described for Fe 3ϩ -TCAS [4] A-500 in the literature, 14,15) it is reasonable that Fe 3ϩ ion is coordinated to the -S-of the epithio groups and the phenolic oxygen atoms of TCAS [4], and is coordinated to TCAS [4] on the modified anion-exchanger with a molar ratio of 1 : 1 as shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…As described for Fe 3ϩ -TCAS [4] A-500 in the literature, 14,15) it is reasonable that Fe 3ϩ ion is coordinated to the -S-of the epithio groups and the phenolic oxygen atoms of TCAS [4], and is coordinated to TCAS [4] on the modified anion-exchanger with a molar ratio of 1 : 1 as shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 75%
“…6,8) Moreover, we have recently demonstrated that some metal complexes of thiacalix [4]arenetetrasulfonate on modified anion-exchangers exhibit high peroxidase-like catalytic activity, and are useful not only for the determination of H 2 O 2 but also for the determination of glucose in control serum as a mimesis of peroxidase in clinical analyses. 14,15) Accordingly, in this study, the catalase-like catalytic activity of metal complexes of thiacalix [4]arenetetrasulfonate on modified anion-exchangers was investigated. To the best of our knowledge, no report has been published on the catalaselike catalytic activity of metal complexes of thiacalix[n]-arenes and calix[n]arenes.…”
mentioning
confidence: 99%
“…[1][2][3][4] Therefore the determination of hydrogen peroxide is important in characterization and selection of honey samples for use as an antimicrobial agent. Several analytical methods have been proposed for the determination of H2O2, including spectrophotometry, [5][6][7][8] spectrofluorometry, 9-13 chemiluminescence [14][15][16][17] and electrochemical techniques. [18][19][20][21] Most of these methods are enzymatic methods that are of interest because of their high sensitivity and selectivity.…”
mentioning
confidence: 99%
“…14 Moreover, we have developed new methods for the spectrophotometric determination of hydrogen peroxide using the peroxidase-like catalytic activity of Fe 3+ -TCAS [4]A-500, and applied them to measurements of glucose and uric acid. 14,15 It has been demonstrated that methods employing Fe 3+ -TCAS [4]A-500 are effective for determining trace amounts of vital compounds in clinical analyses.…”
mentioning
confidence: 99%